Effectiveness of Spotify-Based Health Podcast Intervention on Reproductive Health Perceptions Among Female Vocational School Adolescents: A Pre-Experimental Study - Anisalal Mu’aisyah; Ni Wayan Dwi Rosmalawati; Irma Afifa; Verlina Maya Gita (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2026)
This study investigated the effectiveness of a Spotify-based health education podcast in improving reproductive health perceptions among adolescent girls at a vocational secondary school in Surabaya, Indonesia. Adolescent girls frequently rely on peers as their primary source of reproductive health information, increasing their vulnerability to misinformation and adverse health outcomes. A pre-experimental one-group pre-test–post-test design was conducted involving 42 female students enrolled in the Culinary Arts programme at SMK Kartika IV, selected through total sampling. Participants completed a validated reproductive health perception questionnaire before and 14 days after exposure to a standardized five-episode podcast series delivered via Spotify, covering menstrual health, personal hygiene, sexually transmitted infections, and adolescent reproductive rights. Changes in perception scores were analyzed using the Wilcoxon signed-rank test, while logistic regression was used for subgroup analyses. The mean perception score increased substantially from 61.4 (SD 8.3) at baseline to 86.8 (SD 5.1) following the intervention, representing a mean improvement of 25.4 points (Z = ?5.68; p < 0.001; effect size r = 0.88). The proportion of participants demonstrating positive reproductive health perceptions increased from 90.4% at baseline to 100% after the intervention. Significant improvements were observed across all age groups and information-source categories. These findings indicate that a short-term reproductive health education intervention delivered through a widely accessible digital audio platform can significantly enhance reproductive health perceptions among adolescent girls and may represent a scalable strategy for strengthening adolescent reproductive health promotion programs in Indonesia.